Anisotropic Learning Amidst the Pandemic - CHAN CHEE MING , (2021)
As opposed to isotropy, anisotropy is the ability of a material to assume different properties in different directions when subjected to physical and mechanical changes. Similarly, anisotropic learning amidst the pandemic has empowered students to adapt to the ‘new normal’, which entails improvising the conventional classroom lessons with the ones that are conducted entirely online. There has been myriad challenges and obstacles along the way, starting with poor internet connectivity in rural residential areas, expensive internet charges and the inevitable deterioration of students’ interest in online learning over time. This makes it especially challenging for students to immerse in a pleasant learning experience, not forgetting the fact that every student who participates in these lessons comes from different backgrounds, cultures, beliefs and morals. However, these individuals share some common attributes: flexibility, endurance and adaptability when participating in virtual classes or sessions. Hence, just like how soil anisotropy is linked to soil stabilization, these students have proven to succeed in overcoming the hurdles and obstacles of online learning through sheer versatility, resilience and perseverance. At the same time, they have managed to alter and enhance their respective abilities while acclimatizing to the new-fangled form of online learning. Ending this preamble with an insightful quote by the great Japanese scholar, Kakuzo Okakura, about the prominence of adaptability, ‘The art of life lies in a constant readjustment to our surroundings’. That is being anisotropic: Flexible, adaptable and ready to learn.